Diagnosing and Mitigating the Risks of Lambs’ Mortality in the Sheep Farms of Kuwait: DOI: 10.48129/kjs.14607 - Burezq, Hana’a; Khalil, Faten (Kuwait Journal of Science, 2023)
A survey study was carried out to investigate mortality of Naeemi lambs of Kuwait on nine sheep farms comprising two governmental farms and seven commercial farms. The survey confirmed that sheep farms in Kuwait suffer from high mortality rate of new borne lambs, particularly in the first three weeks of birth, and it is a serious problem since the mortality rate ranges between 15 to 50%. Total red meat demand of Kuwait is met by Naeemi sheep as they are able to survive in local harsh climate. Therefore, minimizing the proportion of death of lambs could have an optimistic consequence in Kuwait sheep industry. In addition, the survey results showed that sheep producers suffer from high abortion rate of ewes, which could range from 2 to 30 % and consequently affect the overall production of sheep in Kuwait. Therefore, more effective and innovative vaccination protocols are required to minimize lamb mortality for Naemi sheeps of Kuwait.